2018
DOI: 10.1371/journal.pbio.2004892
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of a voltage-gated sodium channel gene in a lineage of electric fish leads to a persistent sodium current

Abstract: Most weakly electric fish navigate and communicate by sensing electric signals generated by their muscle-derived electric organs. Adults of one lineage (Apteronotidae), which discharge their electric organs in excess of 1 kHz, instead have an electric organ derived from the axons of specialized spinal neurons (electromotorneurons [EMNs]). EMNs fire spontaneously and are the fastest-firing neurons known. This biophysically extreme phenotype depends upon a persistent sodium current, the molecular underpinnings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…Brains of related species consist mainly of homologous neurons-neurons that share the same developmental origin-and behavior evolution may result from changes in the connectivity or physiology of homologous neurons [2]. Several studies have begun to elucidate how changes in homologous neurons have contributed to behavioral evolution [3][4][5][6][7][8][9][10][11][12]. But a satisfying answer to the broad evolutionary questions posed above requires a systematic methodology to identify and functionally manipulate homologous neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Brains of related species consist mainly of homologous neurons-neurons that share the same developmental origin-and behavior evolution may result from changes in the connectivity or physiology of homologous neurons [2]. Several studies have begun to elucidate how changes in homologous neurons have contributed to behavioral evolution [3][4][5][6][7][8][9][10][11][12]. But a satisfying answer to the broad evolutionary questions posed above requires a systematic methodology to identify and functionally manipulate homologous neurons.…”
Section: Introductionmentioning
confidence: 99%
“…These include genes for steroid receptors and enzymes in steroidogenic pathways, as well as various ion channels that likely control the continuous firing frequency of PN neurons. Thompson et al (2018) , identified a novel voltage-gated Na+ channel ( scn4ab1 ) expressed in the EMNs that resulted from a gene duplication within apteronotids. This channel has amino acid substitutions that prevent it from closing completely.…”
Section: Contributions Of Molecular Studies To the Neuroethology Of Social Behaviormentioning
confidence: 99%
“…A striking example of the independent evolution of persistent sodium currents is in the specialized Na v 1.4 channel isoforms for the muscle-derived electric organs of weakly-electric fish, which can generate electrical pulses in excesses of 1 kHz for sensing their nocturnal environment and the electro-communication with other fish ( Thompson et al, 2018 ). The electromotor neurons of weakly-electric fish can fire at a faster rate of any known animal neuron, using a persistent sodium current generated from the modification of its structural elements for inactivation (S4-S5 linker of Domain IV) of their Na v 1.4 channels ( Thompson et al, 2018 ).…”
Section: “Persistent” Sodium Currents Are Common In Different Invertementioning
confidence: 99%